The Circ-CYP24A1-miR-224-PRLR Axis Impairs Cell Proliferation and Apoptosis in Recurrent Miscarriage - Su, Yan; Xu, Jiani; Gao, Rufei; Liu, Xiaoli; Liu, Taihang; Li, Cong; Ding, Yubin; Chen, Xuemei; He, Junlin; Liu, Xueqing; Li, Chunli; Qi, Hongbo; et al. (Frontiers in Physiology, 2022)
Aim: Recurrent miscarriage (RM) is associated with numerous clinical factors. However, some RM occurred without specific factors. It has been revealed that some molecules such as hormones, miRNAs and transcription factorsare involved in RM through regulating proliferation, apoptosis etc. However, mechanism of RM has not yet been identified clearly. Circular RNAs (circRNAs) as a class of endogenous noncoding RNAs often serve as sponges for miRNAs or bind to proteins participating in biological processes. However, the functional role of circRNAs in uterine decidua of patients with early RM is still unclear. Here we aimed to investigate the mechanisms of circ-CYP24A1 in RM. Methods:Dual-Luciferase Activity Assaywas designed to analysis the bonding relationship between circ-CYP24A1 and miR-224, miR-224 and PRLR. RT-PCR was performed to examine the level of circ-CYP24A1 and miR-224 in decidual and Ishikawa cells. ISH and IHC were used to observe the expression of circ-CYP24A1 and PRLR in decidual. Western blot was conducted to test the expression level of PRLR, proliferation and apoptosis related markers in Ishikawa cells after circ-CYP24A1 or PRLR silencing. Results: In this study, based on the microarray analysis data, we identified the high level of circ-CYP24A1 and PRLR in decidua of patients with early RM. Based on the bioinformatics prediction,the binding relationship between circ-CYP24A1 and miR-224 as well as miR-224 and PRLR were verified. Functional experiments demonstrated that circ-CYP24A1 regulated proliferation and apoptosis by binding to and inhibits miR-224, thereby increasing PRLR expression. Taken together, this study provides new insights into the mechanism of RM. Conclusion:In this paper, we demonstrated that circ-CYP24A1 involved in RM through impairing the balance of cell proliferation and apoptosis by sponging miR-224, thereby regulating PRLR.